Ultrasound-guided injection of platelet-rich plasma in chronic Achilles and patellar tendinopathy() - Ferrero, G. (Elsevier, 2012)
PURPOSE: The efficacy of platelet-rich plasma (PRP) in the treatment and healing of chronic tendinopathy through stimulation of cell proliferation and total collagen production has been demonstrated by both in vitro and in vivo studies. The aim of this study is to evaluate the effectiveness of ultrasound (US)-guided autologous PRP injections in patellar and Achilles tendinopathy. MATERIALS AND METHODS: Autologous PRP was injected under US-guidance into the Achilles and patellar tendons (30 Achilles tendons, 28 patellar tendons) in 48 prospectively selected patients (30 males, 18 females, mean age 38 ± 16 years, range 20–61 years). All patients were previously evaluated according to the Victoria Institute of Sport Assessment (VISA) scale, which assessed pain and activity level, and they all underwent US of the tendon before treatment and at follow-up after 20 days and 6 months. Statistical analysis was performed with Chi-square and Wilcoxon tests. RESULTS: 20 days after PRP injection the patients presented a non-significant improvement of clinical symptoms. At the 6-month follow-up VISA score increased from a mean value of 57–75.5 (p < .01). US evaluation revealed a reduction of hypoechoic areas in 26 tendons (p < .01) associated with a widespread improvement of fibrillar echotexture of the tendon and reduced hypervascularity at power Doppler. CONCLUSION: PRP injection in patellar and Achilles tendinopathy results in a significant and lasting improvement of clinical symptoms and leads to recovery of the tendon matrix potentially helping to prevent degenerative lesions. US-guidance allows PRP injection into the tendon with great accuracy.